2017
DOI: 10.1016/j.arabjc.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of graphite-SiO 2 /Al 2 O 3 /Nb 2 O 5 -methylene blue (GRP-SiAlNb-MB) composite for electrochemical determination of dopamine

Abstract: In the present paper an amperometric sensor based on graphite-SiO 2 /Al 2 O 3 /Nb 2 O 5 -methylene blue (GRP-SiAlNb-MB) composite has been successfully prepared for dopamine (DA) determination in real samples. The electrochemical behavior of DA at the GRP-SiAlNb-MB has been evaluated by employing cyclic voltammetry. The best ratio (m/m) of GRP-SiAlNb-MB composite was found to be 1:0.54. Under optimized conditions (pH 7.5 in 0.15 mol L À1 phosphate buffer) the amperometry method responds linearly to DA from 5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 39 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Sivasankar et al (2018) introduced a new hierarchical mesoporous graphite oxide (HMGO) with Al 2 O 3 for the identification of caffeic acid in red wine samples using a modified GCE. For the detection of glycine, Alam et al Giarola et al (2017) identified that graphite-SiO 2 /Al 2 O 3 /Nb 2 O 5 -methylene blue (GRP-SiAlNb-MB) composite was suitable for the detection of dopamine, DA, in real and pharmaceutical samples with good detection limit. Other works by (Ganjali et al, 2017a;Ganjali et al, 2017b;Ganjali et al, 2018) Rakib et al (2019) and was used for the modification of GCE as a chemical sensor for sensing hazardous chemical 3,4-diaminotoluene.…”
Section: Aluminum Oxide Based Biosensorsmentioning
confidence: 99%
“…Sivasankar et al (2018) introduced a new hierarchical mesoporous graphite oxide (HMGO) with Al 2 O 3 for the identification of caffeic acid in red wine samples using a modified GCE. For the detection of glycine, Alam et al Giarola et al (2017) identified that graphite-SiO 2 /Al 2 O 3 /Nb 2 O 5 -methylene blue (GRP-SiAlNb-MB) composite was suitable for the detection of dopamine, DA, in real and pharmaceutical samples with good detection limit. Other works by (Ganjali et al, 2017a;Ganjali et al, 2017b;Ganjali et al, 2018) Rakib et al (2019) and was used for the modification of GCE as a chemical sensor for sensing hazardous chemical 3,4-diaminotoluene.…”
Section: Aluminum Oxide Based Biosensorsmentioning
confidence: 99%
“…Various types of materials have been applied for sensing development, including metallic origin materials such as Pt, [4] Al2O3, [5] MgO, [6,7] TiO2, [8] Au-SiO2 nanocomposites; [9] carbon derivative materials like carbon powder, [10] graphene, [11][12][13] carbon nanotubes, [14][15][16] and combination of them. [17][18][19] Because of its inherent properties, such as its nano-2D structure and excellent mechanical and electrical properties, graphene is one of the most promising candidates.…”
Section: Introductionmentioning
confidence: 99%